2021
DOI: 10.47391/jpma.462
|View full text |Cite
|
Sign up to set email alerts
|

A CBCT based evaluation of root proximity of maxillary posterior teeth to sinus floor in a subset of Pakistani population

Abstract: Objectives: To evaluate the vertical relationship of the roots of maxillary posterior teeth with maxillary sinus floorand its association with age, gender and bilateral jaw symmetry. Method: The cross-sectional study was conducted at a tertiary care hospital in Karachi from June to December 2018, and comprised patients who visited the dental clinics and underwent cone-beam computed tomography scans. The scans were evaluated in the axial, coronal and sagittal planes and roots were classified using Jungs classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Whereas our study showed that the maxillary mesiobuccal roots were within the maxillary sinus as designated by the negative sign. 17 In our study evaluation of proximity in both males and females show that there is no significant difference, but Von Arx et al found that the sinus was closer to the roots in men than women. This was due to better root formation and longer roots in men.…”
Section: Discussionmentioning
confidence: 44%
“…Whereas our study showed that the maxillary mesiobuccal roots were within the maxillary sinus as designated by the negative sign. 17 In our study evaluation of proximity in both males and females show that there is no significant difference, but Von Arx et al found that the sinus was closer to the roots in men than women. This was due to better root formation and longer roots in men.…”
Section: Discussionmentioning
confidence: 44%